2015
DOI: 10.1037/abn0000058
|View full text |Cite
|
Sign up to set email alerts
|

Poor self-control and harsh punishment in childhood prospectively predict borderline personality symptoms in adolescent girls.

Abstract: Developmental theories of borderline personality disorder (BPD) propose that harsh, invalidating parenting of a child with poor self-control and heightened negative emotionality often leads to a coercive cycle of parent-child transactions that increase risk for BPD symptoms such as emotion dysregulation. Although parenting practices and child temperament have previously been linked with BPD, less is known about the prospective influences of caregiver and child characteristics. Using annual longitudinal data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 94 publications
(131 reference statements)
3
50
0
2
Order By: Relevance
“…However, youth are not only receiving and responding to social cues but also actively evoking others' behavior. Thus, children help to create their own environments from infancy onward (Cicchetti & Cohen, 2006;Hallquist et al, 2015). Temperamentally vulnerable youth often make substantial demands on caregivers, which has an effect on socialization and skill acquisition (Crowell, Yaptangco, & Turner, 2016;Stepp, Whalen, Scott, et al, 2014).…”
Section: Early Socialization and Sex-typical Trajectoriesmentioning
confidence: 99%
“…However, youth are not only receiving and responding to social cues but also actively evoking others' behavior. Thus, children help to create their own environments from infancy onward (Cicchetti & Cohen, 2006;Hallquist et al, 2015). Temperamentally vulnerable youth often make substantial demands on caregivers, which has an effect on socialization and skill acquisition (Crowell, Yaptangco, & Turner, 2016;Stepp, Whalen, Scott, et al, 2014).…”
Section: Early Socialization and Sex-typical Trajectoriesmentioning
confidence: 99%
“…Em relação ao país de origem dos autores dos artigos acima citados, ficou assim compilado: um da Croácia; dois sendo multinacionais: Reino Unido e Estados Unidos e Itália com Alemanha; dois do Canadá; um da China e cinco dos Estados Unidos; todos tiveram seus trabalhos publicados em periódicos de grande impacto. Dentre os artigos selecionados, considerando a titulação dos primeiros autores, seis foram publicados por psicólogos clínicos 14,15,16,17,18,19,20 e quatro por psiquiatras 5,21,22,23 , importante considerar que houve a interação interdisciplinar entre seus autores. Corroborando que os profissionais da área da saúde mental (psicologia e psiquiatria) evidência um maior interesse em publicar assuntos relacionados ao tratamento do adolescente com o TPB, observando que em todos os manuscritos encontrados relataram a importância ou nomearam a família no tratamento realizado com os adolescentes.…”
Section: Resultsunclassified
“…Consistent with these findings, Jovev et al (2013) also showed that maltreatment acted as a moderator of the relationship between temperament dimensions and increases in BPD over time. In further support of the notion of complex prospective transactional processes, Hallquist, Hipwell, and Stepp (2015) recently demonstrated reciprocal influences among harsh parenting, self-control, and negative emotion-This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Trend #3 Development: Complex Transactional Developmental Momentioning
confidence: 90%